In vitro evaluation of the cytotoxicity and cellular uptake of CMCht/PAMAM dendrimer nanoparticles by glioblastoma cell models - Pojo, Marta (2013)
Glioblastoma (GBM) is simultaneously the most common and most malignant subtype tumor of the central nervous system. These are particularly dramatic diseases ranking first among all human tumor types for tumor-related average years of life lost and for which curative therapies are not available. Recently, the use of nanoparticles as drug delivery systems (DDS) for tumor treatment has gained particular interest. In an attempt to evaluate the potential of carboxymethylchitosan/poly(amidoamine) (CMCht/PAMAM) dendrimer nanoparticles as a DDS, we aimed to evaluate its cytotoxicity and internalization efficiency in GBM cell models. CMCht/PAMAM-mediated cytotoxicity was evaluated in a GBM cell line (U87MG) and in human immortalized astrocytes (hTERT/E6/E7) by MTS and double-stranded DNA quantification. CMCht/PAMAM internalization was assessed by double fluorescence staining. Both cells lines present similar internalization kinetics when exposed to a high dose (400 μg/mL) of these nanoparticles. However, the internalization rate was higher in tumor GBM cells as compared to immortalized astrocytes when cells were exposed to lower doses (200 μg/mL) of CMCht/PAMAM for short periods (<24 h). After 48 h of exposure, both cell lines present ~100 % of internalization efficiency for the tested concentrations. Importantly, short-term exposures (1, 6, 12, 24, and 48 h) did not show cytotoxicity, and long-term exposures (7 days) to CMCht/PAMAM induced only low levels of cytotoxicity in both cell lines (~20 % of decrease in metabolic activity). The high efficiency and rate of internalization of CMCht/PAMAM we show here suggest that these nanoparticles may be an attractive DDS for brain tumor treatment in the future.